PROCESSING ADDITIVES AND RHEOLOGICAL PROPERTIES OF MOLDED PHENOLIC PLASTICS - P. V. Surikov; N. L. Shembel; A. A. Yurkin; A. V. Petrogradsky; V. D. Sevruk; I. D. Simonov-Emelyanov (Тонкие химические технологии)
By the method of capillary viscosimetry, the melt flow curves of the molded phenolic resin and its compositions with lubricant, plasticizer and their mixture were obtained. It was shown that the size (diameter) of the capillary channel influences the dependence of the effective shear rate on the shear stress (flow curves) of the studied compositions. Such rheological behavior of the compositions during flow is associated with the effect of sliding along the surface of the capillary wall. According to the Mooney method, the dependences of the effective shear rate at given values of shear stress on the reciprocal of the capillary radius are plotted. The function of the slip velocity on the shear stress on the capillary wall is characterized in terms of the slip coefficient, which relates the shear stress on the capillary wall to the velocity of the composition along it. For the studied compositions, the total flow through the capillary was divided into volume fractions, one of which is associated with a shear flow; the other is determined by the slip effect. It has been shown that the introduction of both a lubricant and a plasticizer into the composition leads to an increase in the fluidity of the compositions. At the same time, adding of lubricant increases the volume fraction of the slip flow. The greatest effect of increasing the fluidity of the composition gives the use of complex modifying additives containing both lubricant and plasticizer.